Directional Atherectomy Followed by a Paclitaxel-Coated Balloon to Inhibit Restenosis and Maintain Vessel Patency: Twelve-Month Results of the DEFINITIVE AR Study. (September 2017) - Zeller, Thomas; Langhoff, Ralf; Rocha-Singh, Krishna J.; Jaff, Michael R.; Blessing, Erwin; Amann-Vesti, Beatrice; Krzanowski, Marek; Peeters, Patrick; Scheinert, Dierk; Torsello, Giovanni; Sixt, Sebastian; Tepe, Gunnar
Abstract : Background—: Studies assessing drug-coated balloons (DCB) for the treatment of femoropopliteal artery disease are encouraging. However, challenging lesions, such as severely calcified, remain difficult to treat with DCB alone. Vessel preparation with directional atherectomy (DA) potentially improves outcomes of DCB. Methods and Results—: DEFINITIVE AR study (Directional Atherectomy Followed by a Paclitaxel-Coated Balloon to Inhibit Restenosis and Maintain Vessel Patency—A Pilot Study of Anti-Restenosis Treatment) was a multicenter randomized trial designed to estimate the effect of DA before DCB to facilitate the development of future end point-driven randomized studies. One hundred two patients with claudication or rest pain were randomly assigned 1:1 to DA+DCB (n=48) or DCB alone (n=54), and 19 additional patients with severely calcified lesions were treated with DA+DCB. Mean lesion length was 11.2±4.0 cm for DA+DCB and 9.7±4.1 cm for DCB ( P =0.05). Predilation rate was 16.7% for DA+DCB versus 74.1% for DCB; postdilation rate was 6.3% for DA+DCB versus 33.3% for DCB. Technical success was superior for DA+DCB (89.6% versus 64.2%; P =0.004). Overall bail-out stenting rate was 3.7%, and rate of flow-limiting dissections was 19% for DCB and 2% for DA+DCB ( P =0.01). One-year primary outcome of angiographic percent diameter stenosis was 33.6±17.7% for DA+DCB versus 36.4±17.6% for DCB ( P =0.48), and clinically driven target lesion revascularization was 7.3% for DA+DCB and 8.0% for DCB ( P =0.90). Duplex ultrasound patency was 84.6% for DA+DCB, 81.3% for DCB ( P =0.78), and 68.8% for calcified lesions. Freedom from major adverse events at 1 year was 89.3% for DA+DCB and 90.0% for DCB ( P =0.86). Conclusions—: DA+DCB treatment was effective and safe, but the study was not powered to show significant differences between the 2 methods of revascularization in 1-year follow-up. An adequately powered randomized trial is warranted. Clinical Trial Registration—: http://www.clinicaltrials.gov . Unique Identifier: NCT01366482.